Innovative Approaches to Suppressing Pseudomonas aeruginosa Growth and Virulence: Current Status and Future Directions - Sandip Patil; Xiaowen Chen; Feiqiu Wen (Cellular Microbiology)
Pseudomonas aeruginosa, an antibiotic-resistant opportunistic pathogen, poses significant challenges in treating infections, particularly in immunocompromised individuals. This review explores current and future innovative approaches to suppress its growth and virulence. We delve into the bacterium’s virulence factors, discussing existing strategies like antibiotics, bacteriophages, probiotics, and small-molecule inhibitors. Additionally, novel approaches, including RNA interference, CRISPR-Cas systems, and nanotechnology, show promise in preclinical studies. Despite advancements, challenges persist, prompting the need for a multifaceted approach targeting various aspects of P. aeruginosa pathogenesis for effective infection management. This review provides a comprehensive perspective on the status and future directions of innovative strategies against P. aeruginosa.